2010
DOI: 10.1186/1471-2148-10-302
|View full text |Cite
|
Sign up to set email alerts
|

A maximum pseudo-likelihood approach for estimating species trees under the coalescent model

Abstract: BackgroundSeveral phylogenetic approaches have been developed to estimate species trees from collections of gene trees. However, maximum likelihood approaches for estimating species trees under the coalescent model are limited. Although the likelihood of a species tree under the multispecies coalescent model has already been derived by Rannala and Yang, it can be shown that the maximum likelihood estimate (MLE) of the species tree (topology, branch lengths, and population sizes) from gene trees under this form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
579
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 592 publications
(602 citation statements)
references
References 68 publications
6
579
3
3
Order By: Relevance
“…When a high level of gene tree heterogeneity occurs in multilocus sequence data, theory and simulations have predicted that concatenation methods can yield misleading results (5,6). By contrast, more recently developed coalescence-based methods estimate a species phylogeny from a collection of gene trees, an approach that allows different genes to have different topologies (4,(7)(8)(9)(10). Simulations and theory have shown that coalescent methods can produce accurate phylogenies from multilocus sequence data that are subject to incomplete lineage sorting (ILS), a major cause of gene tree heterogeneity (4,(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…When a high level of gene tree heterogeneity occurs in multilocus sequence data, theory and simulations have predicted that concatenation methods can yield misleading results (5,6). By contrast, more recently developed coalescence-based methods estimate a species phylogeny from a collection of gene trees, an approach that allows different genes to have different topologies (4,(7)(8)(9)(10). Simulations and theory have shown that coalescent methods can produce accurate phylogenies from multilocus sequence data that are subject to incomplete lineage sorting (ILS), a major cause of gene tree heterogeneity (4,(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…For the 273 loci, we created 100 multilocus bootstraps (Seo, 2008) that resample both loci within the dataset and bases within a locus. We used three methods of species tree inference: (1) accurate species tree algorithm (ASTRAL; Mirarab et al., 2014), (2) maximum pseudo‐likelihood of estimating species trees (MP‐EST; Liu, Yu, & Edwards, 2010), and (3) species trees from average ranks of coalescence (STAR; Liu et al., 2009). In these analyses, the A. sagrei sample designated the outgroup.…”
Section: Methodsmentioning
confidence: 99%
“…Individual gene trees were estimated using maximum likelihood using the program RAxML [31]. Because gene tree discordance potentially can prevent recovery of the species tree with concatenated data [32], we used maximum pseudo-likelihood estimates of species trees (MP-EST) [33] to estimate the species tree from the set of gene trees. MP-EST has been shown to be statistically consistent in estimating the species tree even in the anomaly zone, and is computationally efficient for a moderate number of taxa, as in this study [33].…”
Section: Methodsmentioning
confidence: 99%